Self Centeredness of Total Graphs W.R.T. D-Distance - V. Ramanjaneyulu, M.; L. N.Varma, P.; Reddy Babu, D. (International Journal of Engineering and Technology, 2018)
In this article using D-distance, we study the self-centeredness of total graphs. We end with some open questions.Â Â